BILANGAN PEROKSIDA, BILANGAN ASAM, DAN KADAR FFA BIODIESEL DENGAN PENAMBAHAN ANTIOKSIDAN DARI KULIT BUAH PISANG KEPOK (Musa paradisiaca Linn.) - Sanjiwani, Ni Made Sukma; Suaniti, Ni Made; Rustini, Ni Luh (Jurnal Kimia (Journal of Chemistry); Vol. 9, No. 2 Juli 2015, 2015)
The peel of banana kepok fruit ( Musa paradisiaca Linn.) contains compound that function as an antioxidant in biodiesel. The purposes of this study were to determine the peroxide number, acid number, and FFA content of biodiesel from waste palm oil with addition of chloroform extract (EKKBPK). Biodiesel was synthesized using esterification reaction of wasted palm oil with methanol (10:1) and by transesterification reaction (4:1), the extract of peel of banana kepok fruit was theen added with various concentration of 0,1 % w/v (A1); 0,2 % w/v (A2); and 0,3 % w/v (A3) to the reaction mixtures. The peroxide number, acid number, and FFA content of synthesized biodiesel obtained in this research were 9.3591 meq peroxide/1000 g; 0.7221 mg KOH/g; and 0.33% repectively; biodiesel without addition of EKKBPK (12.2746 meq peroxide/1000 g; 0.6492 mg KOH/g; and 0.30%); and biodiesel with addition of EKKBPK 0.1 % w/v (11,1878 meq peroxide/1000 g; 0,4814 mg KOH/g; and 0.22%); 0.2 % w/v (9.7508 meq peroxide/1000 g; 0.3501 mg KOH/g; and 0.16%); and 0.3 % w/v (12.2512 meq peroxide/1000 g; 0.5217 mg KOH/g; and 0.24%). The acid numbers of those biodiesel were in acordance to the acid number of SNI 04-7182-2006. The addition of 0.2 % w/v EKKBPK on biodiesel showed the lowest peroxide number, acid number, and FFA content threfore it was the most effective in inhibiting the oxidation reaction of biodiesel.
Keywords: biodiesel, waste palm oil, peel of banana kapok fruit, oxidation reaction